Spectral study of carbon-13 N.M.R. of three Parkia gums - León de Pinto, Gladys; Martínez, Maritza; Beltrán, Olga; Rivas, Carlos; Torres, María Angélica (Ciencia, 2014)
Analytical data ofgum from the seed pods oí Parkiapéndula, growing in Costa Rica, and the Nigerian gum exudates from Parkia bicolor and Parkia biglobosa have been published. Galactose, arabinose, glucuronic acid and its 4-0-methyl analogue are present in the three Parkia gums investigated. C-NMRspectra ofthe polysaccharides, isolated from the Parkia gums corroborated the presence ofthe sugars mentioned above and the absence of rhamnose. The polysaccharides of P. bicolor and P. biglobosa showed very similar spectra. They contain the signáis due to the sugars present in the polysaccharide structures. The spectrum of P. péndula original gum looks like the spectrum of and a - arabínan, but its dearabinosilatíon led a better resolution of the signáis due to galactose and uronic acid residues. The spectral evidences found in this work are according with the sugar and methylation analyses.